Urinary micro-RNA biomarker detection using capped gold nanoslit SPR in a microfluidic chip. Issue 12 (21st June 2015) - Mousavi, Mansoureh Z.; Chen, Huai-Yi; Lee, Kuang-Li; Lin, Heng; Chen, Hsi-Hsien; Lin, Yuh-Feng; Wong, Chung-Shun; Li, Hsiao Fen; Wei, Pei-Kuen; Cheng, Ji-Yen
<x xml:space="preserve">Abstract</x> Diagnosis of acute kidney injury by detecting urinary miRNA using capped gold nanoslit SPR in a microfluidic chip.